VOCATIONAL EDUCATION, WORK AND KNOWLEDGE PRODUCTION - Naira Lisboa Franzoi; Maria Clarice Rodrigues de Oliveira (Editora da Universidade de Santa Cruz do Sul, 2015)
The paper presents the case study about a reasearch developed in a vocational education school, by two students. They are workers from a region of tobacco industry in the interior of Rio Grande do Sul/Brazil. The focus is on how the dialogue between the school knowledge, and the students' experiencial knowledge took place. It is a theoretical essay of seeing an use of Three Poles Dynamic Device - methodological tool proposed by Ergology. The concepts of human activity, work, knowledge and Three Poles Dynamic Device (DD3P) are the theoretical framework of the study. Our objetctiv is to give visibility to a successful experience in a public school whose audience are young and adult workers , and exploring the possibilities of using a theoretical and methodological tool that aims to promote dialogue between academic knowledge and knowledge engaged in work activity. Thus, we believe we are contributing to the teaching practice and the theoretical - methodological field , still under construction.